2014
DOI: 10.13175/swjpcc121-14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of an automated systemic inflammatory response syndrome (sirs) / organ dysfunction alert: a system-based patient safety project

Abstract: Objective: We have employed our electronic medical record (EMR) in an effort to identify patients at the onset of severe sepsis through an automated analysis that identifies simultaneous occurrence of systemic inflammatory response syndrome (SIRS) and organ dysfunction. The purpose of this study was to determine the positive predictive value of this alert for severe sepsis and other important outcomes in hospitalized adults. Design: Prospective cohort. Setting: Banner Good Samaritan Medical Center, Phoenix AZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Our lactate decision support system has a positive predictive value (PPV) for acute lifethreatening clinical events that is superior to that of our previous "sepsis alert" (27) and to those reported in several reviews of EWSs. One review of 39 EWSs reported PPVs ranging from 13.5-26.1% (34), and another review of 25 systems reported a median PPV of 36.7% with interquartile range 29.3-43.8% (34).…”
Section: * Our Data Indicate That Rrt Activation Would Occur About Twmentioning
confidence: 75%
See 3 more Smart Citations
“…Our lactate decision support system has a positive predictive value (PPV) for acute lifethreatening clinical events that is superior to that of our previous "sepsis alert" (27) and to those reported in several reviews of EWSs. One review of 39 EWSs reported PPVs ranging from 13.5-26.1% (34), and another review of 25 systems reported a median PPV of 36.7% with interquartile range 29.3-43.8% (34).…”
Section: * Our Data Indicate That Rrt Activation Would Occur About Twmentioning
confidence: 75%
“…As stated in the new definition of sepsis, "Nonspecific SIRS criteria such as pyrexia or neutrophilia will continue to aid in the general diagnosis of infection" (7). Although these criteria are nonspecific, they appear to be relatively sensitive for sepsis (7,27). Our lactate DSS has excellent discriminant accuracy for predicting inpatient mortality (AUROC=0.80).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations